Evaluation of Diagnostic Accuracy of Low-Dose CT Scan in Acute Appendicitis - Hammad Ahmad Saqib, Umama Saeed, Muhammad Amin, Hira Bushra, Nida Fatima, Atqa Firdous, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Low-dose computed tomography has been introduced as an alternative option for the diagnosis of diseases in adults, however, limited studies have been conducted in children Objective: To evaluate the diagnostic accuracy of low-dose CT for diagnosis of acute appendicitis in children as compared to ultrasound and CT scan. Methodology: A retrospective study was conducted in the Radiology Department of Chaudhary Pervez Ellahi Institute of Cardiology, Multan from March 2022 to March 2023. A total of 250 pediatric patients younger than 10 years admitted to the hospital with signs of acute appendicitis were selected for the study.All patients underwent low-dose CT, abdominal ultrasound, or standard-dose CT. Results: The methods did not differ significantly with respect to sensitivity for appendicitis diagnosis (96.9%, 95.9%, and 94.8%, p=0.789) and visualization of the perforated appendix (100%, 86.2%, and 100%).There was no significant difference between the diagnostic sensitivity of methods in early childhood (100%, 100%, and 94.8%, p=0.292) and late childhood (94%, 93.1%, and 94.8%, p=0.831). However, specificity (94%, 77.9%, and 98%, p=0.370) and PPV (97%, 90.3%, and 99%, p=0.011) in middle childhood were significantly difference between groups. Conclusion: Low-dose CT has comparable effectiveness and accuracy for diagnosis of pediatric appendicitis as compared to ultrasound and standard-dose CT. Keywords: Appendicitis, Computed Tomography, Ultrasonography, Ultrasound